Transforming communities in ASEAN: Efforts by Malaysia’s global reach programme. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2015)
The Association of Southeast Asian Nations (ASEAN) was formed on 8th August 1967 as an alliance in promoting economic and political cooperation as well as regional stability (ASEAN, 2014). The objectives of ASEAN establishment are to accelerate the economic growth, social progress, and cultural development in the Southeast Asia region, as well as to promote regional peace and stability, active collaboration, and mutual assistance of common interests among the members (ASEAN, 2014).